Sport legacy of the Olympic Games London 2012 - Girginov, V.; Hills, L.; Kuznetsova, Z. (The Russian Journal of Physical Education and Sport, 2016)
This paper addresses the little explored issue of the link between hosting the Olympic games and sports participation in the host country within the framework of sustainable sports legacy. It takes a process oriented approach suggesting that Olympic legacies are constructed and not given, and explores the role of the International Olympic Committee and the UK government in framing the sports legacy. Material. The paper draws from relevant literature and two original case studies, and analyses five main processes involved in legacy construction. Methods. Scientific- methodical literature analysis and summarizing, testing, methods of mathematical statistics. Results. The IOC framed the legacy as a three- stage process: a framework developed by the IOC, a vision produced by the candidate city, and implementation secured by the OCOG. The framework was supported politically ( new rules in the Olympic Charter and the IOC Manual for Candidate cities, 2001), legally ( through the Host City Contract between the IOC, the host city and the OCOG), and scientifically( through the OGI). The legacy framework was rationalized and operationalized through the OGI, which measures the economic, environmental and social impact of the games through a set of indicators over a period of 12 years and four reports. Conclusion. The concept of sustainable Olympic sports development legacy is a controversial and contested one. However, its appeal is that it offers grounds for agreement between Olympic aspirations for social progress and equality and the striving for growth by staging faster, higher, stronger and ever better games. It is difficult to imagine, however, how sustainable sports participation can be achieved without addressing the issues of the rights of different communities and sports and Olympic versus non- Olympic sports development. As the House of Commons Report warned: the substantial financial contribution by Sport England to the 2012 Games need not necessarily have a major effect on programmes to enhance participation in sport at community level. However, there is a clear risk, if we are not careful, that programmes outside the capital may suffer because of the focus on London and in particular in sports which are either not part of the Olympics or which are not recognized as mainstream Olympic sports.